Importance of domestic guidelines for women with urinary incontinence - Síssi Sisconeto de Freitas; Maria Cristina Cortez Carneiro Meirelles; Adriana Clemente Mendonça
Introduction The importance of domestic guidelines as a help in the treatment of urinary incontinence (UI) is evident, but its influence on the quality of life (QoL) of incontinent women, when applied without supervision, is unknown. Objective To evaluate the influence of domestic guidelines for the treatment of UI on the QoL of incontinent women. Methods This is a quasi-experimental before and after study. Seventy one women with UI and a mean age of 53.47 (± 14.21) years were assessed, instructed with the aid of an illustrative and explanatory folder and reassessed after six months using the King's Health Questionnaire (KHQ). KHQ data were analyzed using the Wilcoxon test for paired samples, with significance level of 5%. Results There was a statistically proven improvement in six of the eight domains and in six of the ten symptoms assessed (p < 0.05). Conclusion We conclude that the domestic guidelines for treatment of UI positively influenced the QoL of the women who participated in this study.